2014
DOI: 10.2478/johr-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Positive Interaction Of Ethanol With Malic Acid In Postharvest Physiology Of Cut Spray Carnation ‘White Natila’

Abstract: In this study, succinic acid (0, 1 and 2 mM), malic acid (0, 1 and 2 mM), ethanol (0, 2 and 4% v/v), and their mixtures were applied as preservative solutions for cut flowers of spread carnation cv. ‘White Natila’ and their effect on the longevity, the amount of absorbed solution, malondialdehyde and chlorophyll content, cell membrane stability, fresh, and dry weight and on a visual quality was determined. A similarity in the effect of malic acid and succinic acid on dry weight and fresh weight loss were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…However, the shortest vase life was obtained in the control recording 8.33 and 7.66 days in the first and second seasons, respectively. Our results seemed to be in agreement with the results of (Begri et al, 2014), on carnation. They found that a preservative solution containing 1 mM malic acid and 4% ethane resulted in the longest vase life (11.1 days compared to 8.9 days in the control).…”
Section: Inflorescence Vase Life (Days)supporting
confidence: 92%
“…However, the shortest vase life was obtained in the control recording 8.33 and 7.66 days in the first and second seasons, respectively. Our results seemed to be in agreement with the results of (Begri et al, 2014), on carnation. They found that a preservative solution containing 1 mM malic acid and 4% ethane resulted in the longest vase life (11.1 days compared to 8.9 days in the control).…”
Section: Inflorescence Vase Life (Days)supporting
confidence: 92%
“…Additionally, postharvest preservation management used in packing houses also influences the quality and storage of fresh commodities, including edible flowers. Among others, ethanol application during postharvest preservation of fresh produce (Han et al, 2006; Tzortzakis and Economakis, 2007; Tzortzakis, 2010) and cut flower (Kaur and Mukherjee, 2013; Begri et al, 2014) has already been examined, while the ethanol application method usually includes dipping rather than vaporization (Begri et al, 2014). The effectiveness of ethanol is related to the increase of the vase life of carnation flowers by preventing the biosynthesis and action of ethylene (Heins and Blakely, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Vriesea incurvata floral scapes even when kept in vases containing only distilled water showed a longevity of 16 days, which can be considered a reasonable vase life in the absence of any other postharvest treatment and higher than the average of many temperate species (Begri et al, 2014;Wu et al, 2016). Although the preservative solutions can be a great way in maintaining flowers, it is well known that not all marketing areas in the Southern Hemisphere apply them.…”
Section: Discussionmentioning
confidence: 96%
“…Carola (Wu et al, 2016), and 8.9 days for Carnation cv. White Natila (Begri et al, 2014). Comparatively, the long period of the longevity of V. incurvata floral scapes, makes it a viable alternative to include as a new product to use as cut flower, both locally and internationally.…”
Section: Introductionmentioning
confidence: 99%